Contribution and Challenges of Community Health Workers in Achieving Sustainable Development Goals - Jyothi Kurapati; Anitha Chandanadur Thippaiah (Medsci Publications, 2022)
Background: Community health workers (CHWs) are a renewed focus in the 2030 SDGs. CHWs support equitable coverage for preventive, promotive, and curative services as healthcare partners. This study aimed to identify the challenges of community health workers (CHWs) in achieving Sustainable Development Goals. Methods: We searched PubMed, Google Scholar, Science Direct, Web of Science, etc., for the published articles between 2015 to 2022. Twenty publications and WHO documents met the inclusion criteria and were analysed and used in the study. Results: Findings show that CHWs are valuable and cost-effective and have the potential to help achieve several SDGs. The top 10 issues faced by CHWs were listed in the research, including Lack of advancement chances, Excessive workload, Insufficient pay, Insufficient staff, Poor management culture, Lack of supervision, Poor interpersonal relationship with supervisors, limited access to technology, A lack of training and Reduced patient care time. The article also proposes critical activities to assist CHWs in achieving the SDGs. Conclusions: CHWs are essential in health care delivery and help expand preventative, promotive, and curative services. Regular evaluation of CHWs' performance is critical for creating health policy and system support that optimizes the utilization of CHWs for SGDs.